Solid-state electrolyte based on inorganic filler modification, and preparation method and application thereof
Patent Information
- Application Number
- CN202510548500.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]现有的技术中,纳米级的二氧化硅球做为无机填料加入到电解质中,容易团聚,从而降低电池的性能
[0049]本发明实施例提供了一种基于无机填料改性的固态电解质的制备方法,首先制备结构式为SiO2@MoS2的无机填料,然后制备含有该无机填料和聚合物的静电纺丝膜,将静电纺丝膜浸泡在原位聚合溶液,取出后组装为固态电池,该固态电池可以是固态锂金属电池,之后对固态电池进行加热处理,使原位聚合溶液在静电纺丝膜上进行原位聚合,最终得到固态电解质,以及含有该固态电解质的固态电池。该制备方法采用成熟的静电纺丝工艺制备得到无机填料均匀分散在聚合物物骨架中的静电纺丝膜,并在静电纺丝膜上浸润原位聚合溶液,组装固态电池过程中在一定温度下使原位聚合溶液原位聚合,制备方法简单易操作,成本低。
Smart Images

Figure CN123018117A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery materials technology, and in particular to a solid electrolyte based on inorganic filler modification, its preparation method, and its application. Background Technology
[0002] Lithium metal, as an anode material, is lightweight, has a high theoretical specific capacity (3860 mAh / g), and a low reduction potential (-3.04 V compared to a standard hydrogen electrode), thus showing broad application prospects in next-generation lithium-ion batteries. When used in conjunction with a high-voltage / high-capacity cathode, lithium metal batteries (LMBs) can achieve energy densities exceeding 300 Whk / g. However, during repeated charge-discharge cycles, active lithium metal readily reacts with the electrolyte, leading to uncontrolled dendrite growth and an unstable solid electrolyte phase (SEI). This process inevitably reduces the coulombic efficiency (CE) and electrochemical performance of lithium polymers. Therefore, improving interfacial compatibility and suppressing lithium dendrite growth are crucial for the stability and safety of LMBs.
[0003] Currently, research reports indicate that silica (SiO2) particles are widely used in fields such as medicine, photonics, and catalysis due to their environmental friendliness, low cost, and ease of production. Recently, silica particles have been developed for modifying the surfaces of polymer (such as PP) separators to improve their thermal stability and electrolyte affinity. Furthermore, silica particles are also used as fillers to enhance the mechanical strength and thermal stability of separators. Additionally, the increased tortuosity resulting from the use of silica particles can increase the ion diffusion path length, which may lead to concentration polarization, thereby increasing cellular resistance and limiting transport capacity.
[0004] Two-dimensional materials, particularly transition metal dihalogen compounds (TMDCs), are attractive candidates for the synthesis of advanced functional materials. Among TMDCs, molybdenum disulfide (MoS2) has attracted significant interest as a lithium-ion battery anode material, replacing graphite anodes, due to its 670 mAh / g capacity. Furthermore, molybdenum disulfide and its derivatives are used in various forms of energy storage systems. Similar to graphite, molybdenum disulfide possesses a layered structure with covalently bonded Mo-S-Mo units forming a hexagonal lattice, with an interlayer spacing of 0.62 nm (compared to 0.34 nm for graphite), facilitating rapid lithium-ion diffusion within the structure. Moreover, theoretical studies indicate that, unlike graphene where lithium ions are strongly bound to defects, lithium ions are loosely adsorbed onto defects in molybdenum disulfide, without hindering diffusion. Molybdenum disulfide also exhibits selective ion transport properties and is used as a lithium-ion conductive film in lithium-ion batteries containing liquid electrolytes.
[0005] In existing technologies, nanoscale silica spheres, when added to the electrolyte as inorganic fillers, tend to agglomerate, thus reducing battery performance. Pure MoS2 materials face several challenges in practical applications, such as low electronic conductivity and irreversible collapse of their two-dimensional layered structure during charge and discharge, resulting in poor electrochemical performance, rapid energy decay, and poor rate capability. Existing polymer solid electrolytes, while possessing some flexibility and improving contact with the lithium metal anode, suffer from lithium dendrite formation during charge-discharge cycles, which can puncture the polymer electrolyte's contact with the cathode, creating micro-short circuits and further affecting battery performance. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a solid-state electrolyte based on inorganic filler modification, its preparation method, and its applications. By growing MoS2 nanosheets on the surface of SiO2 to form a coating structure, a SiO2@MoS2 core-shell inorganic filler is obtained. The MoS2 nanosheets facilitate the dispersion of nanoscale SiO2 particles and connect SiO2 nanospheres together, improving the elastic modulus of the solid-state electrolyte and effectively preventing lithium dendrite penetration. Furthermore, both SiO2 and MoS2 can effectively promote the dissociation of lithium salts, improving ionic conductivity. Simultaneously, the SiO2@MoS2 material exhibits high-temperature resistance, enabling the battery to remain stable at high temperatures, meeting the requirements of solid-state batteries. To a certain extent, the SiO2@MoS2 material can catalyze the formation of a stable SEI film rich in Li3N, reducing interfacial impedance.
[0007] To achieve the above objectives, in a first aspect, embodiments of the present invention provide a solid electrolyte based on inorganic filler modification, the solid electrolyte comprising: an electrospinning membrane, and a gel solid electrolyte polymerized in situ on the electrospinning membrane;
[0008] The electrospun film comprises: a polymer, and an inorganic filler uniformly dispersed in the polymer; wherein the inorganic filler comprises: silica nanospheres, and a molybdenum disulfide coating layer covering the outer surface of the silica nanospheres; the inorganic filler has the structural formula SiO2@MoS2;
[0009] The gel solid electrolyte is formed by heating an electrospinning membrane containing the in-situ polymerization solution, causing the in-situ polymerization solution to polymerize in situ on the electrospinning membrane.
[0010] The in-situ polymerization solution comprises: organic monomers, initiators, plasticizers, and lithium salts;
[0011] The gel solid electrolyte comprises: a copolymer, and the plasticizer and the lithium salt filling the voids in the network structure of the copolymer; the copolymer is formed by polymerization of the organic monomers initiated by the initiator.
[0012] Preferably, the inorganic filler accounts for 30% to 62% of the total mass of the electrospun membrane;
[0013] The particle size Dv50 of the inorganic filler is 100nm to 300nm;
[0014] The polymer includes one or more of the following: polyvinylidene fluoride (PVDF), ethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA).
[0015] Preferably, the organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA); the initiator includes: azobisisobutyronitrile (AIBN);
[0016] The plasticizer includes one or more of the following: succinic anionyl nitrile (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC); the mass percentage of the plasticizer to the total mass of the gel solid electrolyte is 20% to 40%.
[0017] The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB); the mass percentage of the lithium salt in the total mass of the gel solid electrolyte is 5% to 20%.
[0018] The heating treatment is performed at a temperature of 60℃ to 70℃ for 6 to 12 hours.
[0019] Secondly, embodiments of the present invention provide a method for preparing a solid electrolyte based on inorganic filler modification as described in the first aspect, the preparation method comprising:
[0020] Step S1: Prepare an inorganic filler with the structural formula SiO2@MoS2; wherein the core of the inorganic filler is a silica nanosphere and the outer shell is a molybdenum disulfide coating layer;
[0021] Step S2: Prepare an electrospun membrane containing the inorganic filler and polymer;
[0022] Step S3, preparing the in-situ polymerization solution, includes: mixing an organic monomer and an initiator to obtain a first liquid; mixing a plasticizer and a lithium salt to obtain a second liquid; and mixing the first liquid and the second liquid to obtain the in-situ polymerization solution.
[0023] Step S4: Immerse the electrospun membrane in the in-situ polymerization solution, remove it and assemble it into a solid-state battery. Heat the solid-state battery to cause the in-situ polymerization solution on the electrospun membrane to polymerize in situ to form a gel solid electrolyte, and finally obtain the solid electrolyte.
[0024] Preferably, step S1, preparing the inorganic filler with the structural formula SiO2@MoS2, specifically includes:
[0025] Step S11: Disperse silica nanospheres in hydrochloric acid aqueous solution to form a first suspension. Perform ultrasonic dispersion treatment and centrifugation treatment on the first suspension in sequence. The centrifuged product is then washed with deionized water until neutral and vacuum dried to obtain activated silica nanospheres.
[0026] Step S12: Activated silica nanospheres are dispersed in anhydrous ethanol, and 3-aminopropyltriethoxysilane (APTES) is added. The mixture is first ultrasonically dispersed, and then heated and stirred to uniformly graft amino groups onto the surface of the activated silica nanospheres to form a second suspension containing SiO2-NH2- groups. The second suspension is centrifuged and washed with anhydrous ethanol at least three times. After vacuum drying, surface amino-modified silica nanospheres are obtained.
[0027] Step S13: Ammonium molybdate tetrahydrate and thiourea are added to a mixed solvent of deionized water and ethanol. The mixture is first ultrasonically dispersed and then stirred at room temperature until the ammonium molybdate tetrahydrate and thiourea are completely dissolved. Then, the surface amino-modified silica nanospheres are added to form a third suspension. The suspension is then ultrasonically dispersed and stirred at room temperature, and then placed in a hydrothermal reactor for hydrothermal reaction to obtain a black suspension.
[0028] Step S14: The black suspension is washed with water and ethanol at least three times, and then vacuum dried to obtain an inorganic filler with the structural formula SiO2@MoS2.
[0029] More preferably, in step S11, the silica nanospheres account for 10wt% to 30wt% of the first suspension; the molar concentration of the hydrochloric acid aqueous solution is 0.5mol / L to 1mol / L; the ultrasonic dispersion treatment time is 15min to 30min; and the centrifugation speed is 5000rpm to 8000rpm, and the centrifugation time is 5min to 10min.
[0030] In step S12, the mass percentage of the activated silica nanospheres to the anhydrous ethanol is 5% to 20%; the APTES accounts for 0.5 wt% to 1 wt% of the second suspension; the ultrasonic dispersion treatment time is 15 min to 30 min; the heating and stirring temperature is 60℃ to 80℃, and the time is 5 hours to 8 hours.
[0031] In step S13, the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:3 to 1:2; the mass ratio of deionized water to ethanol is 1:2 to 1:1; the surface amino-modified silica nanospheres account for 0.5 wt% to 1 wt% of the third suspension; the ultrasonic dispersion time is 15 min to 30 min; the stirring time at room temperature is 1 hour to 2 hours; and the hydrothermal reaction temperature is 180℃ to 220℃, and the time is 12 hours to 24 hours.
[0032] In step S14, the drying temperature is 60℃~80℃ and the drying time is 11 hours~13 hours.
[0033] Preferably, step S2, the preparation of the electrospun membrane containing the inorganic filler and the polymer, specifically includes:
[0034] Inorganic fillers are added to an organic solvent and ultrasonically dispersed for 30 to 60 minutes to form a mixed solution with a solid content of 8 wt% to 20 wt%; wherein the solvent includes N,N-dimethylformamide (DMF) and / or acetone;
[0035] The polymer is added to the mixed solution and stirred at 60°C to 70°C for 3 to 12 hours to form a uniform spinning solution; the polymer includes one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA); the polymer accounts for 5 wt% to 15 wt% of the mixed solution.
[0036] The spinning solution is placed into two syringes and transferred to an electrospinning machine for electrospinning to obtain an electrospinned membrane. The diameter of the syringe is 0.5 mm to 1 mm, and the distance from the needle tip to the electrospinning collection plate is 15 cm to 20 cm. The electrospinning speed is 0.5 ml / h to 1 ml / h, the humidity is 20 RT% to 30 RT%, the temperature is 20℃ to 30℃, and the voltage is 10 KV to 20 KV.
[0037] The electrospun membrane is placed in an oven and dried at 50℃~80℃ for 6 hours~12 hours. The dried electrospun membrane is then rolled using a roller press at a pressure of 5MPa~10MPa to obtain an electrospun membrane containing the inorganic filler and polymer.
[0038] Preferably, in step S3, the organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA).
[0039] The initiator includes: azobisisobutyronitrile (AIBN);
[0040] The plasticizer includes one or more of the following: succinic anhydride (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC);
[0041] The lithium salt includes one or more of the following: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB);
[0042] The mass ratio of ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA) is [2-3]:[2-3]:[4-6].
[0043] The mass percentage of the azobisisobutyronitrile in the total mass of the first liquid is 1% to 2%.
[0044] The mass ratio of the plasticizer to the lithium salt is [1:1] to [5:1];
[0045] The volume ratio of the first liquid to the second liquid is [1:1] to [1:3].
[0046] Preferably, in step S4, the soaking time is 12 to 24 hours; the heating temperature is 60°C to 70°C, and the heating time is 6 to 12 hours.
[0047] Thirdly, embodiments of the present invention provide a solid-state battery, the solid-state battery comprising the solid electrolyte modified with inorganic fillers as described in the first aspect, or the solid electrolyte modified with inorganic fillers prepared by the preparation method described in the second aspect.
[0048] This invention provides a solid electrolyte based on inorganic filler modification, its preparation method, and its application, which have the following technical effects:
[0049] This invention provides a method for preparing a solid electrolyte based on inorganic filler modification. First, an inorganic filler with the structural formula SiO2@MoS2 is prepared. Then, an electrospun membrane containing the inorganic filler and a polymer is prepared. The electrospun membrane is immersed in an in-situ polymerization solution, removed, and assembled into a solid-state battery, which can be a solid-state lithium metal battery. The solid-state battery is then heated to allow the in-situ polymerization solution to polymerize in situ on the electrospun membrane, ultimately yielding a solid electrolyte and a solid-state battery containing the solid electrolyte. This preparation method utilizes a mature electrospinning process to prepare an electrospun membrane in which the inorganic filler is uniformly dispersed in a polymer framework. The in-situ polymerization solution is then immersed in the electrospun membrane, and during the solid-state battery assembly process, the in-situ polymerization solution is polymerized in situ at a certain temperature. The preparation method is simple, easy to operate, and low in cost.
[0050] The solid electrolyte based on inorganic filler modification and the solid battery containing the solid electrolyte prepared by the preparation method provided in this embodiment of the invention have the following advantages:
[0051] (1) The solid electrolyte based on inorganic filler modification provided in this embodiment of the invention has a high elastic modulus: Since the inorganic filler in the electrospun membrane is a nano-sized silica sphere (SiO2) coated with molybdenum disulfide (MoS2), the inorganic filler is easier to disperse in the polymer mixed solution, making the inorganic filler in the obtained electrospun membrane more uniformly distributed. Furthermore, the rigid core of the nano-sized silica sphere and the layered shell of MoS2 form a "rigid-flexible" structure, which can improve the elastic modulus of the solid electrolyte, effectively block lithium dendrites from penetrating, and thus improve the mechanical properties of the solid electrolyte.
[0052] (2) The solid electrolyte based on inorganic filler modification provided in this embodiment of the invention has high ionic conductivity: the interlayer spacing (approximately 0.62 nm) of the molybdenum disulfide (MoS2) coating layer of the inorganic filler can be Li + Providing a low-barrier transport path, similar to an "ion highway," the hydroxyl groups (-OH) on the surface of silica nanospheres (SiO2) and the sulfur atoms at the edges of MoS2 can promote the dissociation of lithium salts (such as LiTFSI), releasing more free Li. + This improves the ionic conductivity of solid electrolytes.
[0053] (3) The solid electrolyte based on inorganic filler modification provided in the embodiments of the present invention has high thermal stability: the high thermal stability (decomposition temperature greater than 1000℃) of silica nanospheres in the solid electrolyte of the present invention and the high temperature resistance of MoS2 work together to keep the solid electrolyte stable at 150℃.
[0054] (4) The solid electrolyte based on inorganic filler modification provided in this embodiment of the invention is formed by in-situ polymerization between the positive electrode and the negative electrode during the assembly of solid batteries. The resulting solid electrolyte has good interfacial compatibility with the electrode. In addition, the coating structure of the inorganic filler makes SiO2 have an inert surface, which can reduce the direct reaction with lithium metal and delay the decomposition of the electrolyte.
[0055] (5) Solid-state batteries assembled using the in-situ polymerization of inorganic filler-modified solid electrolytes provided in the embodiments of the present invention have good cycle performance and safety. Attached Figure Description
[0056] Figure 1 A flowchart illustrating the preparation method of a solid electrolyte based on inorganic filler modification provided in this embodiment of the invention.
[0057] Figure 2 (a) is a scanning electron microscope (SEM) image of the inorganic filler prepared in Example 1 of the present invention.
[0058] Figure 2 (b) is a magnified SEM image of the inorganic filler prepared in Example 1 of the present invention.
[0059] Figure 3 (a) is a SEM image of the surface of the lithium negative electrode sheet after the coin cell assembled in Example 1 of the present invention has been disassembled after 500 cycles.
[0060] Figure 3 (b) is a SEM image of the surface of the lithium negative electrode sheet after the coin cell assembled in Comparative Example 1 of the present invention was disassembled after 500 cycles.
[0061] Figure 4 The graph shows the cycle capacity retention and coulombic efficiency of the coin cells assembled in Example 1 and Comparative Example 1 of this invention after 500 cycles at 2C. Detailed Implementation
[0062] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0063] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0064] This invention provides a solid electrolyte based on inorganic filler modification, comprising: an electrospinning membrane, and a gel solid electrolyte polymerized in situ on the electrospinning membrane.
[0065] The electrospun film includes a polymer and an inorganic filler uniformly dispersed in the polymer; wherein the inorganic filler includes silica nanospheres and a molybdenum disulfide coating layer covering the outer surface of the silica nanospheres.
[0066] The inorganic filler is designed with the structural formula SiO2@MoS2. The mass of the inorganic filler accounts for 30% to 62% of the total mass of the electrospun film.
[0067] The particle size Dv50 of the inorganic filler is 100nm to 300nm, and can be any value within this range, such as 100nm, 120nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, etc., but is not limited to the listed values; other unlisted values within this range are also applicable. Particle size Dv50 refers to the volume median particle size of the material, representing the particle size corresponding to 50% of the material's volume distribution, a meaning known in the art. The particle size Dv50 of the inorganic filler provided in this embodiment of the invention can be determined using instruments and conventional methods known in the art. Specifically, according to the standard "ISO 13320:2020 Particle size distribution—Laser diffraction method", the particle size Dv50 can be determined using a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0068] The polymers include one or more of the following: polyvinylidene fluoride (PVDF), ethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA).
[0069] Gel solid electrolyte is formed by heating an electrospun membrane containing an in-situ polymerization solution, causing the in-situ polymerization solution to polymerize in situ on the electrospun membrane; the heating temperature is 60℃~70℃, and the heating time is 6 hours~12 hours.
[0070] The in-situ polymerization solution comprises: organic monomers, initiators, plasticizers, and lithium salts. Specifically, the organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA); the initiator includes: azobisisobutyronitrile (AIBN); the plasticizer includes: one or more of succinic anionyl nitrile (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC); the plasticizer accounts for 20% to 40% of the total mass of the gel solid electrolyte.
[0071] The gel solid electrolyte comprises a copolymer, and a plasticizer and a lithium salt filling the voids in the network structure of the copolymer; the copolymer is formed by the polymerization of organic monomers initiated by an initiator.
[0072] The lithium salts include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB); the mass percentage of the lithium salts in the total mass of the gel solid electrolyte is 5% to 20%.
[0073] This invention provides a method for preparing the above-mentioned solid electrolyte based on inorganic filler modification, such as... Figure 1 As shown, it includes the following steps:
[0074] Step S1: Prepare an inorganic filler with the structural formula SiO2@MoS2;
[0075] Specifically, the core of the SiO2@MoS2 inorganic filler is a silica nanosphere, and the outer shell is a molybdenum disulfide coating layer; the preparation process of the SiO2@MoS2 inorganic filler includes:
[0076] Step S11: Silica nanospheres are dispersed in hydrochloric acid aqueous solution to form a first suspension. The first suspension is then subjected to ultrasonic dispersion and centrifugation. The centrifuged product is washed with deionized water until neutral and then vacuum dried to obtain activated silica nanospheres. The silica nanospheres comprise 10wt%–30wt% of the first suspension; the molar concentration of the hydrochloric acid aqueous solution is 0.5mol / L–1mol / L; the ultrasonic dispersion time is 15min–30min; and the centrifugation speed is 5000rpm–8000rpm for 5min–10min.
[0077] Step S12: Activated silica nanospheres are dispersed in anhydrous ethanol, and 3-aminopropyltriethoxysilane (APTES) is added. The mixture is first ultrasonically dispersed, then heated and stirred to uniformly graft amino groups onto the surface of the activated silica nanospheres, forming a second suspension containing SiO2-NH2- groups. The second suspension is centrifuged and washed at least three times with anhydrous ethanol, then vacuum dried to obtain surface-amino-modified silica nanospheres. The mass percentage of activated silica nanospheres to anhydrous ethanol is 5%–20%; APTES accounts for 0.5 wt%–1 wt% of the second suspension; the ultrasonic dispersion time is 15 min–30 min; and the heating and stirring temperature is 60℃–80℃ for 5 hours–8 hours.
[0078] Step S13: Ammonium molybdate tetrahydrate and thiourea are added to a mixed solvent of deionized water and ethanol. The mixture is first ultrasonically dispersed, then stirred at room temperature until completely dissolved. Then, amino-modified silica nanospheres are added to form a third suspension. This suspension is then subjected to ultrasonic dispersion and stirring at room temperature, followed by a hydrothermal reaction in a hydrothermal reactor to obtain a black suspension. The mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:3 to 1:2; the mass ratio of deionized water to ethanol is 1:2 to 1:1; the amino-modified silica nanospheres comprise 0.5 wt% to 1 wt% of the third suspension; the ultrasonic dispersion time is 15 min to 30 min; the stirring time at room temperature is 1 hour to 2 hours; and the hydrothermal reaction temperature is 180℃ to 220℃ for 12 hours to 24 hours.
[0079] Step S14: The black suspension is washed with water and ethanol at least three times, and then dried to obtain an inorganic filler with the structural formula SiO2@MoS2; wherein the vacuum drying temperature is 60℃~80℃ and the time is 11 hours~13 hours.
[0080] Step S2: Prepare an electrospun membrane containing inorganic fillers and polymers;
[0081] Specifically, the preparation of electrospun membranes containing inorganic fillers and polymers includes:
[0082] Inorganic fillers are added to an organic solvent and ultrasonically dispersed for 30 to 60 minutes to form a mixed solution with a solid content of 8 wt% to 20 wt%; wherein the solvent includes N,N-dimethylformamide (DMF) and / or acetone;
[0083] The polymer is added to the mixed solution and stirred at 60℃~70℃ for 3 hours to 12 hours to form a uniform spinning solution; the polymer includes one or more of the following: polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA); the polymer accounts for 5wt% to 15wt% of the mixed solution.
[0084] The spinning solution was placed into two syringes and transferred to an electrospinning machine for electrospinning to obtain an electrospinned membrane. The diameter of the syringes was 0.5 mm to 1 mm, and the distance from the needle to the electrospinning collection plate was 15 cm to 20 cm. The electrospinning speed was 0.5 ml / h to 1 ml / h, the humidity was 20 RT% to 30 RT%, the temperature was 20℃ to 30℃, and the voltage was 10 kV to 20 kV.
[0085] The electrospun membrane is placed in an oven and dried at 50℃~80℃ for 6 hours to 12 hours. The dried electrospun membrane is then rolled using a roller press at a pressure of 5MPa~10MPa to obtain an electrospun membrane containing inorganic fillers and polymers.
[0086] Step S3, preparing the in-situ polymerization solution, includes: mixing an organic monomer and an initiator to obtain a first liquid; mixing a plasticizer and a lithium salt to obtain a second liquid; and mixing the first liquid and the second liquid to obtain the in-situ polymerization solution.
[0087] The organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoroamyl acrylate (OFPA);
[0088] Initiators include: azobisisobutyronitrile (AIBN);
[0089] Plasticizers include one or more of the following: succinic anhydride (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC);
[0090] Lithium salts include one or more of the following: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB);
[0091] The mass ratio of ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA) is [2-3]:[2-3]:[4-6].
[0092] The mass percentage of azobisisobutyronitrile (AIBN) in the total mass of the first liquid is 1% to 2%.
[0093] The mass ratio of plasticizer to lithium salt is [1:1] to [5:1];
[0094] The volume ratio of the first liquid to the second liquid is [1:1] to [1:3].
[0095] Step S4: Immerse the electrospun membrane in the in-situ polymerization solution, remove it and assemble it into a solid-state battery. Heat the solid-state battery to allow the in-situ polymerization solution on the electrospun membrane to polymerize in situ to form a gel solid electrolyte, and finally obtain the solid electrolyte.
[0096] The soaking time is 12 to 24 hours; the heat treatment temperature is 60℃ to 70℃, and the heating time is 6 to 12 hours.
[0097] The in-situ polymerization process specifically includes:
[0098] (1) Azobisisobutyronitrile (AIBN) decomposes to generate free radicals: AIBN decomposes at 60℃~80℃. The azo group (N=N) in the AIBN molecule undergoes homolytic cleavage to generate two 2-cyano-2-propyl free radicals (CH3)2C(CN).
[0099] (2) Free radicals (CH3)2C(CN) attack the double bonds (C=C) of trimethylolpropane triacrylate (TMPTA), ethylene ethylene carbonate (VEC), and octafluoropentyl acrylate (OFPA) to initiate chain polymerization. Each TMPTA molecule contains three acrylate groups, forming a three-dimensional cross-linked network. The vinyl groups of VEC and the propylene groups of octafluoropentyl acrylate participate in the polymerization, forming copolymers with the segments of TMPTA. Among them, octafluoropentyl acrylate (OFPA) can improve the wettability of the in-situ polymerization solution, allowing the in-situ polymerization solution to better wet the electrospun film.
[0100] (3) The above copolymer and the polymer of the electrospun film form a network structure, and the plasticizer and lithium salt fill the gaps in the network structure to eventually form a gel solid electrolyte.
[0101] The solid electrolyte based on inorganic filler modification prepared by the preparation method provided in this invention can be assembled with positive and negative electrode sheets to form a solid-state battery, which includes, but is not limited to, an all-solid-state lithium metal battery.
[0102] There are no special restrictions on the negative electrode sheet used; any negative electrode sheet that can be used in solid-state batteries is acceptable. The negative electrode sheet is classified according to the negative electrode active material it contains, including but not limited to: lithium metal sheet, silicon-carbon negative electrode sheet, graphite negative electrode sheet, graphene negative electrode sheet, transition metal negative electrode sheet, etc. The negative electrode sheet is prepared using conventional methods.
[0103] There are no special restrictions on the positive electrode sheet used; any positive electrode sheet that can be used in solid-state batteries is acceptable. The positive electrode sheet is classified according to the positive active material it contains, including but not limited to: positive electrode sheets containing lithium cobalt oxide, positive electrode sheets containing ternary materials, positive electrode sheets containing lithium manganese oxide, positive electrode sheets containing lithium iron phosphate, etc. Among them, the ternary material can be NCM523, NCM622, NCM811, etc. The positive electrode sheet is prepared using conventional methods.
[0104] The solid-state battery based on the inorganic filler-modified solid electrolyte provided in this embodiment of the invention has nanoscale inorganic filler SiO2@MoS2 uniformly distributed inside the inorganic filler-modified solid electrolyte, and the interlayer spacing of the molybdenum disulfide (MoS2) coating layer can be Li + Providing a low-barrier transport pathway, the hydroxyl groups (-OH) on the surface of silica nanospheres (SiO2) and the sulfur atoms at the edges of MoS2 can promote the dissociation of lithium salts, releasing more free Li.+ This improves the ionic conductivity of the solid-state electrolyte, thereby enhancing the rate performance of the solid-state battery. Furthermore, MoS2 facilitates the dispersion and prevents agglomeration of nano-sized SiO2 particles, allowing silica nanospheres to be dispersed and arranged within the electrospun membrane, thus improving the mechanical properties of the solid-state electrolyte and enhancing the safety of the solid-state battery. Additionally, the inorganic filler-modified solid-state electrolyte provided by this invention has an electrospun membrane framework with excellent wetting properties. In-situ polymerization is carried out by impregnating the electrospun membrane framework with the polymerization solution, forming an in-situ polymerized gel solid-state electrolyte on the framework. This in-situ polymerization method improves the interfacial contact between the electrode and the solid-state electrolyte, enhancing the chemical stability of the solid-state battery. In summary, the solid-state battery using the inorganic filler-modified solid-state electrolyte provided in this invention exhibits good rate performance and cycle performance.
[0105] To better understand the technical solution provided by the present invention, the following uses several specific examples to illustrate the solid electrolyte and its characteristics based on inorganic filler modification.
[0106] Example 1
[0107] This embodiment provides a solid electrolyte modified with inorganic fillers and a coin cell containing the solid electrolyte, as detailed below.
[0108] Step 1: Prepare an inorganic filler with the structural formula SiO2@MoS2. The specific process is as follows:
[0109] (1) 200g of silica nanospheres were dispersed in a hydrochloric acid aqueous solution with a molar concentration of 1mol / L to form a first suspension. The first suspension was ultrasonically dispersed for 30min to remove surface impurities and increase hydroxyl density. Then, it was centrifuged at 8000rpm for 10min to obtain the centrifuged product. The centrifuged product was washed with deionized water until neutral and then vacuum dried to obtain activated silica nanospheres. The silica nanospheres accounted for 20wt% of the first suspension.
[0110] (2) Activated silica nanospheres were dispersed in anhydrous ethanol, and 3-aminopropyltriethoxysilane (APTES) was added. The mixture was first ultrasonically dispersed for 30 min, and then heated and stirred at 60 °C for 6 hours to uniformly graft amino groups onto the surface of the activated silica nanospheres to form a second suspension containing SiO2-NH2- groups. The product of the second suspension was centrifuged at 8000 rpm for 10 min and washed three times with anhydrous ethanol. After vacuum drying, surface amino-modified silica nanospheres were obtained. The mass percentage of activated silica nanospheres to anhydrous ethanol was 10%, and APTES accounted for 1 wt% of the second suspension.
[0111] (3) Ammonium molybdate tetrahydrate and thiourea were added to a mixed solvent of deionized water and ethanol. The mixture was first ultrasonically dispersed for 30 min, and then stirred at room temperature for 1 hour to completely dissolve the ammonium molybdate tetrahydrate and thiourea. Then, amino-modified silica nanospheres were added to form a third suspension. The suspension was then ultrasonically dispersed for 30 min and stirred at room temperature for 1 hour. Finally, the suspension was placed in a hydrothermal reactor and subjected to a hydrothermal reaction at 200°C for 18 hours to obtain a black suspension. The total mass of ammonium molybdate tetrahydrate and thiourea accounted for 1 wt% of the third suspension, and the mass ratio of ammonium molybdate tetrahydrate to thiourea was 1:3. The mass ratio of deionized water to ethanol in the mixed solvent was 1:1. The amino-modified silica nanospheres accounted for 0.5 wt% of the third suspension.
[0112] (4) The black suspension was washed three times with water and ethanol, and then vacuum dried at 60°C for 12 hours to obtain an inorganic filler with the structural formula SiO2@MoS2 and a particle size Dv50 of 300nm.
[0113] Step 2: Prepare an electrospun membrane containing inorganic fillers and polymers, specifically including the following steps;
[0114] (1) Add the inorganic filler prepared in step one to DMF and ultrasonically disperse for 45 min to form a first suspension of a mixed solution with a uniformly dispersed solid content of 10 wt%.
[0115] (2) Add the polymer PVDF to the mixed solution and stir at 60°C for 6 hours to form a uniform spinning solution; wherein the polymer accounts for 10 wt% of the mixed solution.
[0116] (3) The spinning solution is placed into two syringes and transferred to an electrospinning machine for electrospinning to obtain an electrospinned membrane. The diameter of the syringe is 0.5 mm, the distance from the needle to the electrospinning collection plate is 15 cm, the electrospinning speed is 0.5 ml / h, the ambient humidity of the electrospinning process is 20 RT%, the temperature is 30 ℃, and the voltage is 15 KV.
[0117] (4) Place the electrospun film in an oven and vacuum dry it at 80°C for 12 hours. Roll the dried electrospun film with a roller press at a pressure of 10MPa to obtain an electrospun film containing inorganic fillers and polymers. Then cut it into round pieces with a diameter of 16.5mm and send them into a glove box for later use.
[0118] Step 3, prepare the in-situ polymerization solution, including the following steps:
[0119] (1) Vinyl carbonate (VEC), trimethylolpropane triacrylate (TRA), octafluoropentyl acrylate (OFPA), and initiator azobisisobutyronitrile (AIBN) were mixed to obtain a first liquid; wherein the mass ratio of VEC, TRA, and OFPA was approximately 2:2:5, and the amount of AIBN added accounted for 1.5 wt% of the total mass of the first liquid. Specifically, the amounts of VEC, TRA, OFPA, and AIBN were 21.89 g, 21.89 g, 54.72 g, and 1.5 g.
[0120] (2) Succinate (SN) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were mixed at a mass ratio of 3:1 and heated at 60°C to obtain a second liquid. SN was 30 g and LiTFSI was 10 g.
[0121] (3) Mix the first liquid and the second liquid at a volume ratio of 1:2 to obtain an in-situ polymerization solution. (The volumes of the first liquid and the second liquid are 50 ml and 100 ml, respectively.)
[0122] Step four: Immerse the electrospun membrane disc prepared in step two in the in-situ polymerization solution prepared in step three for 24 hours. After removal, assemble it with a commercial lithium iron phosphate cathode and a commercial lithium sheet to form a solid-state battery (i.e., an all-solid-state lithium metal battery, also known as a coin cell). Heat the coin cell at 65°C for 8 hours to allow the in-situ polymerization solution on the electrospun membrane to polymerize in situ and form a gel solid electrolyte. Finally, obtain a solid electrolyte modified with inorganic fillers and a coin cell containing the solid electrolyte.
[0123] SEM images of the inorganic packing material prepared in the embodiments of the present invention are as follows: Figure 2 (a) and Figure 2 As shown in (b), where, Figure 2 (b) is Figure 2 (a) shows a magnified view of a portion of the silicon dioxide nanospheres, where molybdenum disulfide is coated on the surface of the nanospheres.
[0124] The performance of the inorganic filler-modified solid electrolyte prepared in the embodiments of the present invention was tested, as follows.
[0125] Testing the performance of the solid electrolyte: First, the electrospun membrane disc prepared in step two was immersed in the in-situ polymerization solution prepared in step three for 24 hours. After removal, it was directly heated at 65℃ for 8 hours to obtain the solid electrolyte. The ionic conductivity, electrochemical window, and elastic modulus of the solid electrolyte were then tested.
[0126] The ionic conductivity of the solid electrolyte was measured using electrochemical impedance spectroscopy (EIS) on an electrochemical workstation. The specific steps included: first, cutting the solid electrolyte into small circular pieces and sandwiching them between two stainless steel (SS) inert electrodes, then inserting them into a battery for testing. To ensure accuracy, the test battery was placed in a temperature-controlled chamber. In the EIS test, the frequency range was set from 0.01 Hz to 1 MHz, and the amplitude voltage was set to 10 mV to accurately measure the electrolyte's resistance. Next, by analyzing the Nyquist impedance spectrum, the ionic conductivity of the electrolyte could be calculated using the following formula: In the determination of ionic conductivity, d in the formula represents the thickness of the electrolyte, R is the volume resistance of the electrolyte read from the Nyquist impedance diagram of EIS, and S represents the effective contact area between the electrolyte and the stainless steel inert electrode. To ensure the accuracy of the measurement, when testing the ionic conductivity at different temperatures, the constant temperature chamber needs to be set to the target temperature and maintained for half an hour to allow the test battery to reach thermal equilibrium. This step ensures the stability of the test environment, thereby allowing for accurate measurement of the ionic conductivity of the electrolyte at various temperatures.
[0127] To determine the safe electrochemical window (the highest withstand voltage of a solid electrolyte), a lithium metal sheet was used as both the reference and counter electrode, while a stainless steel sheet (SS) was used as the working electrode. During the experiment, a lithium / solid electrolyte / stainless steel (Li|SPE|SS) battery was assembled in a glove box, and then linear sweep voltammetry (LSV) was performed in a constant-temperature oven at room temperature. The scan rate was set to 1 millivolt per second (mV / s), scanning from the open-circuit voltage to 6V.
[0128] The elastic membrane content, i.e., mechanical strength, of the solid electrolyte is tested using a universal tensile testing machine. The electrolyte is cut into a 5cm × 1cm rectangle, and its thickness is measured using calipers. The cut solid electrolyte is then clamped onto the tensile testing machine, the area and thickness are input, the tensile speed is set to 1cm / min, and the termination condition is fracture. The test is then performed.
[0129] Cycle capacity retention of the coin cell: To test the cycle stability of the electrolyte, the capacity retention of the coin cell (LFP cathode | solid electrolyte | lithium metal anode) assembled in this embodiment was tested after 500 cycles at a 2C current density using a Blue Electric tester. Detailed test data are shown in Table 1.
[0130] After disassembling the coin cell that had undergone 500 cycles, SEM testing was performed on the surface of the lithium metal anode. The SEM images are shown below. Figure 3 As shown in (a).
[0131] The cycle capacity and coulombic efficiency curves of this embodiment are shown below. Figure 4 As shown in the figure, the horizontal axis represents the number of cycles (CycleNumber, cycles), the right vertical axis represents the coulombic efficiency (%), and the left vertical axis represents the specific capacity (mAh / g). It can be seen that the coin cell battery in this embodiment retains 93.8% of its cycle capacity after 500 cycles, demonstrating good cycle performance.
[0132] Example 2
[0133] This embodiment provides a solid electrolyte modified with inorganic filler and a coin cell containing the solid electrolyte. The difference from Example 1 is that the polymer added in step two (2) is a mixture of PAN and PEO with a mass ratio of 3:7. The other preparation processes are the same as in Example 1.
[0134] The solid electrolyte based on inorganic filler modification prepared in this embodiment and the coin cell containing the solid electrolyte were tested. The test method was the same as in Example 1, and the test data are detailed in Table 1.
[0135] Example 3
[0136] This embodiment provides a solid electrolyte modified with inorganic filler and a coin cell containing the solid electrolyte. The difference from Embodiment 1 is that the mass ratio of VEC, TRA, and OFPA in step three (1) is 2:2:6. The other preparation processes are the same as in Embodiment 1.
[0137] The solid electrolyte based on inorganic filler modification prepared in this embodiment and the coin cell containing the solid electrolyte were tested. The test method was the same as in Example 1, and the test data are detailed in Table 1.
[0138] Example 4
[0139] This embodiment provides a solid electrolyte modified with inorganic fillers and a coin cell containing the solid electrolyte, which differs from Embodiment 1 in step one:
[0140] (1) 200g of silica nanospheres were dispersed in a hydrochloric acid aqueous solution with a molar concentration of 0.5mol / L to form a first suspension. The first suspension was ultrasonically dispersed for 15min to remove surface impurities and increase hydroxyl density. Then, it was centrifuged at 5000rpm for 10min to obtain the centrifuged product. The centrifuged product was washed with deionized water until neutral and then vacuum dried to obtain activated silica nanospheres. The silica nanospheres accounted for 10wt% of the first suspension.
[0141] (2) APTES accounted for 0.5 wt% of the second suspension.
[0142] (3) The total mass of ammonium molybdate tetrahydrate and thiourea accounts for 1.5 wt% of the third suspension, and the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:3; the mass ratio of deionized water to ethanol in the mixed solvent is 1:2; and the surface amino-modified silica nanospheres account for 1 wt% of the third suspension.
[0143] The other preparation processes are the same as in Example 1.
[0144] The solid electrolyte based on inorganic filler modification prepared in this embodiment and the coin cell containing the solid electrolyte were tested. The test method was the same as in Example 1, and the test data are detailed in Table 1.
[0145] Example 5
[0146] This embodiment provides a solid electrolyte modified with inorganic fillers and a coin cell containing the solid electrolyte, which differs from Embodiment 1 in step one:
[0147] (1) 200g of silica nanospheres were dispersed in a hydrochloric acid aqueous solution with a molar concentration of 0.7mol / L to form a first suspension. The first suspension was ultrasonically dispersed for 15min to remove surface impurities and increase hydroxyl density. Then, it was centrifuged at 7000rpm for 10min to obtain the centrifuged product. The centrifuged product was washed with deionized water until neutral and then vacuum dried to obtain activated silica nanospheres. The silica nanospheres accounted for 30wt% of the first suspension.
[0148] (2) APTES accounted for 0.7 wt% of the second suspension.
[0149] (3) The total mass of ammonium molybdate tetrahydrate and thiourea accounts for 1.5 wt% of the third suspension, and the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:2.5; the mass ratio of deionized water to ethanol in the mixed solvent is 1:1.5; and the surface amino-modified silica nanospheres account for 0.7 wt% of the third suspension.
[0150] The other preparation processes are the same as in Example 1.
[0151] The solid electrolyte based on inorganic filler modification prepared in this embodiment and the coin cell containing the solid electrolyte were tested. The test method was the same as in Example 1, and the test data are detailed in Table 1.
[0152] To better illustrate the effects of the embodiments of the present invention, a comparative example is provided to be made with the embodiments described above.
[0153] Comparative Example 1
[0154] The difference between this comparative example and Example 1 is that the step one, which involves preparing the inorganic filler with the structural formula SiO2@MoS2, is omitted, and the inorganic filler is not added in step two (1). Instead, the polymer PVDF is directly added to the solvent DMF and stirred at 60°C for 6 hours to form a uniform spinning solution, with PVDF accounting for 10 wt% of the spinning solution. The resulting solid electrolyte does not contain the SiO2@MoS2 inorganic filler. All other preparation processes are the same as in Example 1.
[0155] The solid electrolyte prepared in this comparative example and the coin cell containing the solid electrolyte were tested using the same methods as in Example 1. The test data are detailed in Table 1. After the coin cell of this comparative example was disassembled after 500 cycles, SEM images were taken of the lithium metal anode surface. The SEM images are shown below. Figure 3 As shown in (b), the lithium metal surface after cycling in Example 1 can be observed. Figure 3 (a) Compared to the lithium metal surface after cycling in Comparative Example 1 Figure 3 (a) The surface is very smooth, indicating that the solid electrolyte based on inorganic filler modification prepared in Example 1 of the present invention can play a role in uniform lithium deposition during cycling and reduce the growth of lithium dendrites.
[0156] The comparative cycle capacity and coulomb efficiency curves are shown below. Figure 4 As shown, the cycle capacity and coulombic efficiency of the coin cell assembled in Comparative Example 1 decay rapidly.
[0157] Comparative Example 2
[0158] The difference between this comparative example and Example 1 is that the step one, which involves preparing the inorganic filler with the structural formula SiO2@MoS2, is omitted, and the inorganic filler is not added in step two (1). Instead, the polymer PVDF is directly added to the solvent DMF and stirred at 60°C for 6 hours to form a uniform spinning solution. PVDF accounts for 10 wt% of the spinning solution, and the resulting electrospun membrane does not contain the SiO2@MoS2 inorganic filler. Furthermore, in step four, the electrospun membrane without the inorganic filler is directly immersed in the second solution prepared in step three of Example 1. All other preparation processes are the same as in Example 1.
[0159] The solid electrolyte prepared in this comparative example and the coin cell containing the solid electrolyte were tested using the same test method as in Example 1. The test data are detailed in Table 1.
[0160] Comparative Example 3
[0161] The difference between this comparative example and Example 1 is that step one, which involves preparing the inorganic filler with the structure SiO2@MoS2, is omitted; the inorganic filler added in step two (1) is silica nanospheres with a particle size Dv50 of 200 nm. The other preparation processes are the same as in Example 1.
[0162] The solid electrolyte prepared in this comparative example and the coin cell containing the solid electrolyte were tested using the same test method as in Example 1. The test data are detailed in Table 1.
[0163] Table 1 summarizes the test data of the button cells assembled in Examples 1-5 and Comparative Examples 1-3:
[0164]
[0165] Table 1
[0166] The comparison of test data in Table 1 shows that the ionic conductivity of Examples 1-3 is slightly higher than that of Comparative Examples 1-3, the safe electrochemical window of Examples 1-5 is significantly higher than that of Comparative Examples 1-3, the elastic modulus (reflecting mechanical properties) of Examples 1-5 is significantly higher than that of Comparative Examples 1-3, and the cycle performance of Examples 1-5 is significantly higher than that of Comparative Examples 1-3. Comparative Example 1, due to the absence of SiO2@MoS2 inorganic filler, has low ionic conductivity and elastic modulus, resulting in low cycle capacity retention. Comparative Example 2, which assembles the battery without in-situ polymerization, leads to unstable interfacial contact between the electrolyte and the negative electrode, hindering lithium-ion migration and significantly reducing cycle performance. Comparative Example 3, using SiO2 material, has lower electrochemical performance and elastic modulus than Examples 1-5. Based on the above data, it can be seen that the SiO2@MoS2 inorganic filler used in this invention, combined with in-situ polymerization, significantly improves the electrochemical performance and mechanical strength of the solid-state lithium metal battery, and also significantly enhances the cycle performance of the solid-state lithium metal battery.
[0167] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A solid electrolyte based on inorganic filler modification, characterized in that, The solid electrolyte includes: an electrospun membrane, and a gel solid electrolyte polymerized in situ on the electrospun membrane; The electrospun film comprises: a polymer, and an inorganic filler uniformly dispersed in the polymer; wherein the inorganic filler comprises: silica nanospheres, and a molybdenum disulfide coating layer covering the outer surface of the silica nanospheres; the inorganic filler has the structural formula SiO2@MoS2; The gel solid electrolyte is formed by heating an electrospinning membrane containing the in-situ polymerization solution, causing the in-situ polymerization solution to polymerize in situ on the electrospinning membrane. The in-situ polymerization solution comprises: organic monomers, initiators, plasticizers, and lithium salts; The gel solid electrolyte comprises: a copolymer, and the plasticizer and the lithium salt filling the voids in the network structure of the copolymer; the copolymer is formed by polymerization of the organic monomers initiated by the initiator.
2. The solid electrolyte according to claim 1, characterized in that, The inorganic filler accounts for 30% to 62% of the total mass of the electrospun membrane; The particle size Dv50 of the inorganic filler is 100nm to 300nm; The polymer includes one or more of the following: polyvinylidene fluoride (PVDF), ethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA).
3. The solid electrolyte according to claim 1, characterized in that, The organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA); the initiator includes: azobisisobutyronitrile (AIBN); The plasticizer includes one or more of the following: succinic anionyl nitrile (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC); the mass percentage of the plasticizer to the total mass of the gel solid electrolyte is 20% to 40%. The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB); the mass percentage of the lithium salt in the total mass of the gel solid electrolyte is 5% to 20%. The heating treatment is performed at a temperature of 60℃ to 70℃ for 6 to 12 hours.
4. A method for preparing a solid electrolyte based on inorganic filler modification as described in any one of claims 1-3, characterized in that, The preparation method includes: Step S1: Prepare an inorganic filler with the structural formula SiO2@MoS2; wherein the core of the inorganic filler is a silica nanosphere and the outer shell is a molybdenum disulfide coating layer; Step S2: Prepare an electrospun membrane containing the inorganic filler and polymer; Step S3, preparing the in-situ polymerization solution, includes: mixing an organic monomer and an initiator to obtain a first liquid; mixing a plasticizer and a lithium salt to obtain a second liquid; and mixing the first liquid and the second liquid to obtain the in-situ polymerization solution. Step S4: Immerse the electrospun membrane in the in-situ polymerization solution, remove it and assemble it into a solid-state battery. Heat the solid-state battery to cause the in-situ polymerization solution on the electrospun membrane to polymerize in situ to form a gel solid electrolyte, and finally obtain the solid electrolyte.
5. The preparation method according to claim 4, characterized in that, Step S1, preparing an inorganic filler with the structural formula SiO2@MoS2, specifically includes: Step S11: Disperse silica nanospheres in hydrochloric acid aqueous solution to form a first suspension. Perform ultrasonic dispersion treatment and centrifugation treatment on the first suspension in sequence. The centrifuged product is then washed with deionized water until neutral and vacuum dried to obtain activated silica nanospheres. Step S12: Activated silica nanospheres are dispersed in anhydrous ethanol, and 3-aminopropyltriethoxysilane (APTES) is added. The mixture is first ultrasonically dispersed, and then heated and stirred to uniformly graft amino groups onto the surface of the activated silica nanospheres to form a second suspension containing SiO2-NH2- groups. The second suspension is centrifuged and washed with anhydrous ethanol at least three times. After vacuum drying, surface amino-modified silica nanospheres are obtained. Step S13: Ammonium molybdate tetrahydrate and thiourea are added to a mixed solvent of deionized water and ethanol. The mixture is first ultrasonically dispersed and then stirred at room temperature until the ammonium molybdate tetrahydrate and thiourea are completely dissolved. Then, the surface amino-modified silica nanospheres are added to form a third suspension. The suspension is then ultrasonically dispersed and stirred at room temperature, and then placed in a hydrothermal reactor for hydrothermal reaction to obtain a black suspension. Step S14: The black suspension is washed with water and ethanol at least three times, and then dried to obtain an inorganic filler with the structural formula SiO2@MoS2.
6. The preparation method according to claim 5, characterized in that, In step S11, the silica nanospheres account for 10wt% to 30wt% of the first suspension; the molar concentration of the hydrochloric acid aqueous solution is 0.5mol / L to 1mol / L; the ultrasonic dispersion treatment time is 15min to 30min; the centrifugation speed is 5000rpm to 8000rpm, and the centrifugation time is 5min to 10min. In step S12, the mass percentage of the activated silica nanospheres to the anhydrous ethanol is 5% to 20%; the APTES accounts for 0.5 wt% to 1 wt% of the second suspension; the ultrasonic dispersion treatment time is 15 min to 30 min; the heating and stirring temperature is 60℃ to 80℃, and the time is 5 hours to 8 hours. In step S13, the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:3 to 1:2; the mass ratio of deionized water to ethanol is 1:2 to 1:1; the surface amino-modified silica nanospheres account for 0.5 wt% to 1 wt% of the third suspension; the ultrasonic dispersion time is 15 min to 30 min; the stirring time at room temperature is 1 hour to 2 hours; and the hydrothermal reaction temperature is 180℃ to 220℃, and the time is 12 hours to 24 hours. In step S14, the vacuum drying temperature is 60℃~80℃ and the time is 11 hours~13 hours.
7. The preparation method according to claim 4, characterized in that, Step S2, the preparation of the electrospun membrane containing the inorganic filler and the polymer, specifically includes: Inorganic fillers are added to an organic solvent and ultrasonically dispersed for 30 to 60 minutes to form a mixed solution with a solid content of 8 wt% to 20 wt%; wherein the solvent includes N,N-dimethylformamide (DMF) and / or acetone; The polymer is added to the mixed solution and stirred at 60°C to 70°C for 3 to 12 hours to form a uniform spinning solution; the polymer includes one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), polypropylene oxide (PPO), and polyurethane acrylate (PUA); the polymer accounts for 5 wt% to 15 wt% of the mixed solution. The spinning solution is placed into two syringes and transferred to an electrospinning machine for electrospinning to obtain an electrospinned membrane. The diameter of the syringe is 0.5 mm to 1 mm, and the distance from the needle tip to the electrospinning collection plate is 15 cm to 20 cm. The electrospinning speed is 0.5 ml / h to 1 ml / h, the humidity is 20 RT% to 30 RT%, the temperature is 20℃ to 30℃, and the voltage is 10 KV to 20 KV. The electrospun membrane is placed in an oven and dried at 50℃~80℃ for 6 hours~12 hours. The dried electrospun membrane is then rolled using a roller press at a pressure of 5MPa~10MPa to obtain an electrospun membrane containing the inorganic filler and polymer.
8. The preparation method according to claim 4, characterized in that, In step S3, the organic monomers include: ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA). The initiator includes: azobisisobutyronitrile (AIBN); The plasticizer includes one or more of the following: succinic anhydride (SN), polyvinyl alcohol (PVA), ethylene carbonate (EC), and propylene carbonate (PC); The lithium salt includes one or more of the following: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), and lithium dioxolane borate (LiBOB); The mass ratio of ethylene ethylene carbonate (VEC), trimethylolpropane triacrylate (TMPTA), and octafluoropentyl acrylate (OFPA) is [2-3]:[2-3]:[4-6]. The mass percentage of the azobisisobutyronitrile in the total mass of the first liquid is 1% to 2%. The mass ratio of the plasticizer to the lithium salt is [1:1] to [5:1]; The volume ratio of the first liquid to the second liquid is [1:1] to [1:3].
9. The preparation method according to claim 4, characterized in that, In step S4, the soaking time is 12 to 24 hours; the heating temperature is 60°C to 70°C, and the heating time is 6 to 12 hours.
10. A solid-state battery, characterized in that, The solid-state battery includes the solid electrolyte modified with inorganic filler as described in any one of claims 1-3, or the solid electrolyte modified with inorganic filler prepared by the preparation method described in any one of claims 4-9.
